Liver of the fish Gymnotus inaequilabiatus and nematode larvae infection: Histochemical features and expression of proliferative cell nuclear antigen. Issue 12 (11th May 2017) - Dezfuli, B Sayyaf; Manera, M; DePasquale, J A; Pironi, F; Giari, L
Abstract: Histopathological lesions due to third‐larval stage of nematode Brevimulticaecum sp. within the liver of a subpopulation of 31 Gymnotus inaequilabiatus from the Pantanal Region (Brazil) were studied with histochemical and immunohistochemical methods. In 93.5% of fish, livers harboured nematode larvae and the intensity of infection ranged from 8 to 293. In livers with highest number of larvae, the hepatic tissue was occupied primarily by the nematodes. Each larva was encircled by focal inflammatory granulomatous reaction. Within the thickness of the granuloma, three concentric layers were recognized: an inner layer of densely packed epithelioid cells, a middle layer of mast cells (MCs) entrapped in a thin fibroblast‐connective mesh and an outer layer of fibrous connective tissue with fibroblasts. Epithelioid cells and fibroblasts within the thickness of the granuloma wall were positive for proliferative cell nuclear antigen (PCNA). Moreover, several hepatocytes in infected liver were immunoreactive to PCNA. Occurrence of rodlet cells and MCs in parenchyma, in close proximity to the encysted nematode larvae and near the blood vessel of infected liver, was observed. Macrophage aggregates (MAs) were numerous within the granulomas and scattered in parenchyma of the infected liver. High quantity of haemosiderin was encountered in MAs and hepatocytes of infected liver.